Empowering learning communities to enhance assessment utilization on merdeka curriculum's PMM platform - Erna Labudasari; Eliya Rochmah; Nur Asyiah; Sri Rohana (Community Empowerment, 2024)
The main problem at SDN Pangrango Cirebon City is the low level of utilization of the 'assessment' feature on the PMM platform. The objectives of this community service activity are: (1) to improve teachers' knowledge and understanding of the importance of learning communities as a means of solving problems in the classroom, (2) to form and develop a learning community, (3) to improve teachers' knowledge of the PMM concept in the Merdeka Curriculum at school, and (4) to improve teachers' skills in using PMM features that can be integrated into classroom learning. The methods applied in this service include: (1) observation and data analysis regarding the learning community and the use of PMM assessments at SDN Pangrango Cirebon City, (2) socialization and mentoring, (3) mentoring in the formation of learning communities and the implementation of assessment features in PMM, and (4) evaluation. The results of this community service activity show that: (1) teachers' knowledge and understanding of learning communities and skills in using assessment features in PMM increased by 92%, (2) the formation of a learning community named "Cakra Sejati", (3) teachers' knowledge of the PMM concept at school increased by 100%, and (4) teachers' skills in integrating PMM features into classroom learning increased by 100%.